Negative ion-gas reaction studies using ion guides and accelerator mass spectrometry II: S-, SO- and Cl- with NO2 and N2O - Eliades, J. A.; Zhao, X. -L.; Litherland, A. E.; Kieser, W. E. (ELSEVIER SCIENCE BV, 2015)
Currently analysis of Cl-36 by accelerator mass spectrometry (AMS) requires large facilities for separation of the isobar S-36. Previously, it has been shown possible to suppress S- by >6 orders of magnitude at low energies in a prototype radio-frequency quadrupole (RFQ) instrument by ion reactions in NO2 gas in the injection line of an AMS system. Reaction products for the negative ions S-, SO- and Cl- with NO2, and S- with N2O, have been surveyed in order to understand isobar attenuation plateaus and the losses of analyte ions. Ion energies were at eV levels, but had a large initial energy spread of at least several eV. Under these conditions, the aggregate total S- and SO- cross sections in NO2 were estimated to be 6.6 x 10(-15) cm(2) and 7.1 x 10(-15) cm(2) respectively and the major reaction channel observed was electron transfer producing NO2-. Other reaction products observed for S- were SO-, SO2-, NS-, and NSO2-. On the other hand, S-, SO- and NS- were found to be largely unreactive with N2O despite the existence of some highly exothermic reaction channels. When Cl- was injected into NO2, reaction products such as CIO- and NO2- were observed only at low levels suggesting that larger Cl- transmissions should be possible with some RFQ design modifications. The CIO- reaction product had only a small attenuation under the experimental conditions, despite having near resonant electron affinity with NO2. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: CHARGE-TRANSFER REACTIONS; ELECTRON-AFFINITIES; NITROUS-OXIDE; LOW-ENERGY; DISSOCIATION